Algorithm for predicting the risk of developing long-Covid in patients with Covid-19 - Voliansky , Andrii; Smilianska, Maiia; Didorenko, Tetiana (Annals of Mechnikov’s Institute, 2023)
A model for predicting the risk of developing Long-covid in patients with Covid-19 is proposed for implementation in the practice of family doctors, pediatricians, therapists, clinical immunologists, and allergists. The essence of the implementation: creation of a model for predicting the risk of developing Long-covid by ranking the leading clinical and laboratory indicators, with the determination of their diagnostic informativeness and scoring, followed by the sum of the points inherent in the patient at the time of calculation.